Daydream Nation : Luz, Espaço e Capitalismo - Ferreira, Sandra Maria Zuzarte Reis da Silva (2019)
Daydream Nation the project here presented experiments the deconstruction of a process of stereoscopic visualization, proposing a reflection on the gaze mediated by an optical apparatus, subject to a “scopic regime”. In a world flooded with light, this work intends the immersion in small perceptions, within the delicate limits of visuality. Daydream Nation takes the title of the musical album from the New York’s Band Sonic Youth, which in 1988 played through sonic explosions the capitalist dystopia of the digital age, with the reproduction of a Gerhard Richter painting on the cover. To look at this image reproduced in a CD, is to stand “in front of time” where echo’s; the vanitas La Madeleine aux deux Flammes de Georges de La Tour, the countless candles lit by the caravagists of Utrecht Utrecht (Gerrit van Honthorst, Hendrick ter Bruggen, Dirck van Barburen) or the confrontation of light and darkness in Caravaggio's tenebrism. The idea of survival got relevance, the “surviving image” or “pathos-image”, Aby Warburg's ghost story as we find reflected in Georges Didi-Huberman's work. This work manifests itself in the form of as a phantasmatic vanitas, which unfolds an anaglyphic stereoscopy image, making appear the vision of a simultaneously lit and unlit candle, a paradox, as the one suggested to Schrödinger by the superposition states of the photon. Democritus of Abdera, the pre-Socratic philosopher believed that human vision depended on projections constantly emanated by bodies, responsible for the transmission of sensations, these emanations where called eidolon, later in latin simulacra. It is precisely a simulacrum that Daydream Nation elaborates. To this end, an multimedia audiovisual installation was elaborated based on an anaglyphic digital photograph that is projected with an HD projector, creating a fantasmatic environment and allowing the viewer to enjoy the "three-dimensional" image of this paradoxical object, the anaglyph candle, simultaneously lit and unlit